Optimization of Exercise Countermeasures for Human Space Flight: Operational Considerations for Concurrent Strength and Aerobic Training - Jones, Thomas W.; Petersen, Nora; Howatson, Glyn (Frontiers in Physiology, 2019)
The physiological challenges presented by space flight and in microgravity (µG) environments are well documented. µG environments can result in declines muscle mass, contractile strength and functional capabilities. Previous work has focused on exercise countermeasures designed to attenuate the negative effects of µG on skeletal muscle structure, function and contractile strength and aerobic fitness parameters. Exposure to µG environments influences both strength and aerobic-type physical qualities. As such, the current exercise recommendations for those experiencing µG involve a combination of strength and aerobic training or “concurrent training”. Concurrent training strategies can result in development and maintenance of both strength and aerobic capabilities. However, terrestrial research has indicated that if concurrent training strategies are implemented inappropriately strength development can be inhibited. Previous work has also demonstrated that the aforementioned inhibition of strength development is dependent on the frequency of aerobic training, modality of aerobic training, the relief period between strength and aerobic training and the intra session sequencing of strength and aerobic training. Whilst time constraints and feasibility are important considerations for exercise strategies in µG, certain considerations could be made when prescribing concurrent strength and aerobic training to those experiencing human space flight. If strength and aerobic exercise must be performed in close proximity, strength should precede aerobic stimulus. Eccentric strength training methods should be considered to increase mechanical load and reduce metabolic cost. For aerobic capacity maintenance cycle and/or rowing based HIIT should be considered and cycle ergometry and/or rowing may be preferable to treadmill running.